Korean Foreign Policy & Korea-Kazakhstan Relations - Kim, Jaechun (My University, 2015)
Major Contents of the Lecture: -Strategic Environment of Korea, -Strategic Challenges of Korea, -Foreign Policy Response of Park Geun-Hye Government, -Geopolitics of Central Asia and Kazakhstan, -Policy Response of Kazakhstan, -Foreign Policy Cooperation of Korea and Kazakhstan.
Keywords: srategic environment of Korea; strategic challenges of Korea; geopolitics of Central Asia and Kazakhstan; foreign policy cooperation of Korea and Kazakhstan; Korea’s foreign policy; environmental protection; climate change; international terrorism; geopolitical location of Kazakhstan; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science